Kebijakan Hukum Pidana Tentang Larangan Pohon Sebagai Alat Peraga Kampanye di Indonesia - Aras Firdaus (DOKTRINA: JOURNAL OF LAW, 2019)
Today trees are inseparable from human life because they are part of the continuity of life but some people themselves neglect trees as living things. when the election campaign party takes place each pair of candidates who take part in the party of democracy we can find a number of trees used as campaign props. Through the criminal law policy instruments contained in the legislation has given strict sanctions. For the sake of the balance of life between nature and humans for the protection and management of the environment, but some people ignore the sanctions of criminal sanctions .. So that the legal protection specifically for the tree rules applied for the continuity of life and the future of humans in the future. The method used in this research is normative juridical analytical descriptive, the aim is to obtain a systematic and detailed picture to answer the problem to be examined. the legal arrangement and protection of trees during the election campaign requires special rules according to the results of the study, so as to minimize environmental damage. The use of trees as campaign props during elections so that law enforcement officials and the relevant government can take legal action against candidates for legislative and executive members.